Feasibility of Electric Vehicle Charging Stations from MV/LV Stations in Small Cities - Roman Sikora; Łukasz Krajewski; Andrzej Popenda; Ewa Korzeniewska (Energies)
Care about the environment is one of the key issues faced by engineers. Among the solutions conducive for reducing CO2 and NOx emissions from road transport is the introduction of electric cars. At the same time, it requires taking care of the infrastructure enabling the charging of electric vehicles in large as well small towns. Since December 2021, an amendment to the Act on Electromobility and Alternative Fuels has been forced in Poland. It introduced the obligation to design and construct buildings in a way that allows the installation of charging stations for electric vehicles. The article proposes a technical criterion for selecting a substation to connect an EV charging station. The criterion was based on the maximum apparent power determined from the transformer’s annual load profile. The transformer profiles were developed using data from the advanced metering infrastructure system with which MV/LV substations are equipped. Thirty-eight of the fifty-five stations were selected for analysis due to insufficient measurement data. In addition to the technical criterion, a social and economic criterion was used to select the location of electric vehicle charging stations.